Factors Influencing Economic Performance of Palm Oil Producers in Akwa Ibom State, Nigeria - Folasade Oluremi Aminu; Justina Umoh (International Journal of Oil Palm, 2020)
The study examined the factors influencing economic performance of palm oil production in Abak Local Government Area of Akwa-Ibom State, Nigeria. The study was based on primary data collected with the aid of pre-tested questionnaire from 120 respondents using multistage sampling technique in the study area. Descriptive statistics and multiple regression analysis were used for data analysis. Results revealed that majority (78%) of the palm oil producers were female with a mean age of about 50 years. The costs and returns analysis indicated that palm oil production was a profitable enterprise with a rate of return of 1.17. The result of the regression analysis revealed that age (p<0.05), education (p<0.01), membership of cooperative society (p<0.05), cost of equipment (p<0.05) and cost of labour were the significant factors influencing economic performance of palm oil producers in the study area. The major constraints faced by the producers were inadequate capital, lack of credit facilities, lack of access to improved inputs and technology, price fluctuation among others. The study recommended that, government, both at the federal and state levels should make credit facilities available and accessible to the palm oil producers at low interest rate in order to sustain and invigorate their economic performance.